2019
DOI: 10.1111/cid.12734
|View full text |Cite
|
Sign up to set email alerts
|

TGF‐β activity in acid bone lysate adsorbs to titanium surface

Abstract: Objectives Osteoblasts lay down new bone on implant surfaces. The underlying cellular mechanism and the spatio‐temporal mode of action, however, remain unclear. It can be proposed that growth factors released upon acidification by osteoclasts adsorb to the implant surface and control the early stages of osseointegration. Methods To simulate bone lysis by osteoclasts, titanium discs were exposed to acid bone lysate (ABL) followed by vigorous washing and seeding of oral f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
20
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(25 citation statements)
references
References 54 publications
5
20
0
Order By: Relevance
“…Furthermore, we showed that PRF-derived TGF-β activity also adsorbs to titanium surfaces. This accords with our earlier observations, which showed that the bone-derived TGF-β activity binds to titanium surfaces 20 . Considering that PRF increases implant stability of dental implants at early stages 5,8 , PRF-derived TGF-β activity may play a critical role in the early phases of osseointegration 20 .…”
Section: Discussionsupporting
confidence: 94%
See 4 more Smart Citations
“…Furthermore, we showed that PRF-derived TGF-β activity also adsorbs to titanium surfaces. This accords with our earlier observations, which showed that the bone-derived TGF-β activity binds to titanium surfaces 20 . Considering that PRF increases implant stability of dental implants at early stages 5,8 , PRF-derived TGF-β activity may play a critical role in the early phases of osseointegration 20 .…”
Section: Discussionsupporting
confidence: 94%
“…This was confirmed by using two independent TGF-β receptor kinase inhibitors thereby blocking the expression of IL11, NOX4 and PRG4. The activation of the Smad2/3 canonical signalling pathway by PRF corroborated our findings, which are in line with previous research on bone-derived TGF-β 20,23 . However, it is unlikely that TGF-β is the only growth factor in PRF lysates capable of inducing a cellular response.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations